The Problems of Neuroparenting Based on Contemporary Islamic Family Law - Ahmad Fauzan; Ilma Silmi Nufus (MILRev: Metro Islamic Law Review, 2024)
Parenting in the family has an impact on the child in all aspects. A contemporary approach to child care will produce an effective and appropriate model for current conditions. Neuroparenting is a contemporary parenting model that is starting to be adopted by many families, especially in Indonesia. This article aims to examine the concept of neuroparenting and find its relevance to contemporary Islamic family law. This article is a qualitative descriptive research whose data was collected from related literature. Literature data was obtained from journals and books that discuss neuroparenting and contemporary Islamic family law, which focuses on discussing the purpose of Islamic law (maqāshid al- al-sharīah). The data was then reduced, presented, and analyzed using an inductive method using hadanah theory and maqāshid al-sharīah to conclude. The research results show that parenting today cannot be separated from developments in science and technology, including neuroparenting. Neuroparenting is a parenting model that uses a medical approach to neuroscience studies. Neuroparenting helps direct child care tailored to gender, age, existing facilities, and infrastructure in the family, especially parents. The implementation of neuroparenting has been under the goals of Islamic law as a form of integration of contemporary science